Education for Responsible Freedom in the Teaching of Karol Wojtyła – John Paul II - Alina Rynio (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
The purpose of this article is an attempt to show, based on selected excerpts from the works of Karol Wojtyła – John Paul II, the specificity of education oriented towards discovering the truth about a man as a worthy, free and responsible being, in need of upbringing. The performed analyses make it possible to see in responsible freedom, the axiological category and the basic attributes of human existence in its relation to the essence of education, the mature humanity of a person and the present day. They indicate the unquestionable value of the message of Karol Wojtyła -John Paul II, in this regard.